Patent Vitello - Intestinal Duct: A Case Report - Thapa, Bijay; Thapa, Anupama; Kayasthya, Anju (Journal of Nepal Paediatric Society, 2021)
A wide variety of anomalies may occur as a result of the vitello- intestinal duct (VID) failing to obliterate completely. These anomalies occur in approximately 2% of the population and may remain silent throughout life or may present incidentally with an intra-abdominal complication. Complete patency of vitello-intestinal duct is the rarest of all the anomalies of VID. We report a case of 27 day old female presenting with pinkish umbilical mass since birth referred to us by a paediatrician as umbilical granuloma, which turned out to be patent vitello- intestinal duct.